Beyond the Alternative Spaces Situated beyond the White Cube - Garnelo-Díez, Isabel; Sedeño Valdellós, Ana (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2019)
The present work is an approach to the study of the production and exhibition of net.art and digital art on the Internet, to make a comparison between the exposure budgets proposed by these new modes of art production in relation to those propoused by traditional exhibition spaces such as museums and art galleries. As an example of digital art exhibition, we will focus on the spanish context, and more specifically on the International Biennial of Digital Art that is known as The Wrong.